2020
DOI: 10.1057/s41293-019-00130-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Thatcherism and Nostalgia: tracing the everyday consequences of holding Thatcherite values

Abstract: With the passing of time and the benefit of hindsight there is, again, growing interest in Thatcherism above all in its substantive and enduring legacy. But, to date at least, and largely due to data limitations, little of that work has focussed on tracing the behavioural consequences, at the individual level, of holding Thatcherite values. That oversight we seek both to identify more clearly and to begin to address. Deploying new survey data, we use multiple linear regression and structural equation modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
2
2
0
1
Order By: Relevance
“…Home ownership in the UK has reached such high rates of saturation that very few of the variables we used are associated with it, and when used as an independent variable, it fails to predict either Neo-Liberalism or Neo-Conservativism. This suggests, in keeping with our argument, that some Thatcherite values and desires have become embedded in UK society (Farrall et al, 2020d). Although home ownership was once a core part of that Thatcherite dream for the aspiration working class, it is now a much more commonly held and normalised desire (a routine expectation).…”
Section: Discussionsupporting
confidence: 84%
“…Home ownership in the UK has reached such high rates of saturation that very few of the variables we used are associated with it, and when used as an independent variable, it fails to predict either Neo-Liberalism or Neo-Conservativism. This suggests, in keeping with our argument, that some Thatcherite values and desires have become embedded in UK society (Farrall et al, 2020d). Although home ownership was once a core part of that Thatcherite dream for the aspiration working class, it is now a much more commonly held and normalised desire (a routine expectation).…”
Section: Discussionsupporting
confidence: 84%
“…While the strong association between nostalgia and the Left falls in line with previous research in the post-Soviet region (White 2007;White 2010), it appears to contradict arguments demonstrating that nostalgic voters support populist and extreme right parties in the West (Farrall et al 2020;Norris and Inglehart 2019;Steenvoorden and Harteveld 2018;Kang 2018;Rensmann 2018;Hibbing, Hayes, and Deol 2017;Kenny 2017). A key theoretical insight concerns the weakness of class-based and economic voting (Pacek 1994;Harper 2000;Tucker 2006).…”
Section: Theoretical Implicationssupporting
confidence: 50%
“…Furthermore, the narratives adopted by the Moldovan Left resemble populist discourses in the West and the authoritarian-conservative ideology in Russia. Given such ideological affinities, it should not come as surprising that nostalgia predicts the vote for the Left in Moldova, while in the West it is associated mostly with the support for the populist radical-right parties (Farrall et al 2020;Norris and Inglehart 2019;Steenvoorden and Harteveld 2018;Rensmann 2018;Hibbing, Hayes, and Deol 2017;Kenny 2017). In this sense, nostalgia functions as an emotion undergirding Euroscepticism both inside and outside the European Union.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies state that behavioral impulses have previously been shown to be effectively applied, and self-monitoring is an essential component of changing behavior for the better (Borg et al, 2020). His transformation of the so-called soul is how people behave and judge the soul based on the behavior shown (Farrall et al, 2021).…”
Section: Resultsmentioning
confidence: 99%